PERANCANGAN SISTEM INFORMASI MANAJEMEN RUMAH SAKIT MODUL FARMASI MENGGUNAKAN METODE TOTAL ARCHITECTURE SYNTHESIS (STUDI KASUS: RUMAH SAKIT UNIVERSITAS MATARAM) - M. Irfan Ramdhani; Dwi Ratnasari; Santi Ika Murpratiwi (Informatics Engineering Dept., Faculty of Engineering, University of Mataram, 2026)
This study aims to optimize the hospital pharmacy process at the University of Mataram Hospital by designing a userfriendly interface for the pharmacy module within the Hospital Management Information System (HMIS). In this research, a combined methodology of Total Architecture Synthesis (TAS) and User-Centered Design (UCD) was employed to ensure both a structured system architecture and a design that meets user needs. For the data collection observations, staff interviews, and literature reviews, which revealed several limitations and confusions in the existing system. The redesigned pharmacy module facilitates structured pharmacy workflow management and supports accurate data reporting. Usability evaluation using the User Experience Questionnaire (UEQ) yielded positive results across all dimensions, with “Stimulation” scoring highest at 1.68 on scale from -3 to +3. These findings indicate that the proposed system design is functional, engaging, and user-friendly, offering improved efficiency and usability in pharmaceutical service operations.Key words: Hospital Management Information System, Total Architecture Synthesis, Pharmacy Module.